Nitrate leaching in soybean rotations without nitrogen fertilizer - Rosolem, Ciro A. [UNESP]; Castoldi, Gustavo [UNESP]; Pivetta, Laercio A. [UNESP]; Ochsner, Tyson E. [UNESP] (Springer, 2018)
Nitrate leaching is a primary pathway of nitrogen loss from agricultural systems, and is affected by both tillage and cropped species. However, there is little information on conservation systems without nitrogen fertilization. Nitrate leaching was assessed in soybean (Glycine max) cropped in rotation with the following cover crops under no-till and chiseling: ruzigrass (Brachiaria ruziziensis), grain sorghum (Sorghum bicolor), pearl millet (Pennisetum glaucum), forage sorghum (Sorghum bicolor), Sunn hemp (Crotalaria juncea), triticale (X Triticosecale) and sunflower (Helianthus annuus). Ruzigrass and grain sorghum cropped in the fall/winter resulted in similar NO3 (-) leaching, which was greater under sunflower than under triticale, likely due to high N uptake and immobilization in plant residues. Sunn hemp as a spring crop resulted in higher NO3 (-) leaching than pearl millet at two locations and forage sorghum at one location likely due to a higher N input by biological fixation. Millet resulted in the lowest N leaching by depleting the soil solution. Chiseling/fallow resulted in higher nitrogen leaching as compared with non-fixing N cover crops. Even when N is not applied, it is important to intensify cropping systems in tropical environments using cover crops with vigorous root systems and high N demand, which prevent N leaching, as well as provides N to the following crop as the straw is mineralized.
Keywords: Nitrate; Sunn hemp; Grain sorghum; Pearl millet; Drainage; No-till